(untitled) (Research, Society and Development, 2021)
Purpose: Third molar surgery is a quite common procedure. Some patients experience pain associated with this situation. The aim of this article aims to discuss non-conventional therapies for the management of postoperative pain associated with third molar surgery. Methods: An extensive literature search was conducted with the keywords “third molar” + “pain” and all articles that excluded already established drugs as analgesics, anti-inflammatories, or therapies such as laser therapy and ozone therapy whereas non-conventional drugs and therapies were retained. Results: The article rated bromelain, honey, hyaluronic acid, nicotine patches, Kinesio tape, TENS, anticonvulsants, curcumin, and melatonin. Some therapies are efficient and safe, while others have not shown promising results. Conclusions: Bromelain and Kinesio tape are considered the most effective non-conventional therapies for controlling postoperative pain, and even with few studies on them, they are therapies with promising results.